Implementasi Sistem Informasi Akuntansi pada BUMDes Multi Guna dalam Menggerakkan Potensi Desa - Putri Nugrahaningsih; Labbaika Dwi Ayu Rahmawati; Denty Arista; Lina Nur Ardila (Jurnal Akuntansi dan Pajak, 2023)
This study aims to implement an information system in the preparation of financial reports for Multipurpose Village Owned Enterprises (BUMDes). The accounting policies are adjusted to the Financial Accounting Standards (SAK) for Micro, Small and Medium Entities (EMKM). Research activities were carried out in the period January to December 2021. To formulate accounting policies, we conducted preliminary studies, observations, interviews and Forum Group Discussions (FGD) with BUMDes leaders and business actors. The implementation of the information system is the application of the PKN STAN excel application in accounting and financial reporting so that the output is able to provide accountability and transparency for the management of BUMDes. Research results in the form of good financial governance are able to contribute to mobilizing village potential through the growing BUMDes business unit.